A method for preparing a wood-based thick carbon electrode material and its application in high-performance capacitors
By preparing natural wood into high-quality wood-based thick carbon electrode materials, the problem of low loading of electrode active substances in the prior art is solved, high capacitance performance and good low temperature resistance are achieved, and the requirements of commercial supercapacitors are met.
Patent Information
- Application Number
- CN202311142783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-09-05
AI Technical Summary
In practical applications, existing carbon-based electric double layer supercapacitors have problems with low loading of electrode active substances and insufficient performance, and it is difficult to meet commercial requirements.
Using natural wood as the base material, wood-based thick carbon electrode material with a unique expanded structure and a developed multi-stage pore structure is prepared by adsorbing a heteroatom-containing activator and carbonizing at high temperature. This material requires no additional additives, maximizing the utilization of electrode space/active materials and improving capacitance performance.
The electrode material with high-quality loads is achieved, meets the requirements of commercial supercapacitors, and shows excellent low-temperature resistance and high initial specific capacitors in low-temperature environments, with good rate performance and cycle stability.
Smart Images

Figure CN117038355B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitors, and in particular relates to a preparation method of a wood-based thick carbon electrode material and application thereof in high-performance capacitors. Background Art
[0002] As a new type of green energy storage device, carbon-based double-layer supercapacitors not only have the characteristics of rapid energy storage and release, but also have the advantages of wide operating temperature range, high power density, ultra-long cycle life, low maintenance cost and safe operation, and have become a current research hotspot. In order to further improve the energy density of capacitors, hybrid capacitors combining carbon-based positive electrodes and metal-based negative electrodes have gradually attracted the interest of researchers. However, there is still a big gap from basic research to practical application of carbon-based double-layer supercapacitors, and it remains the main challenge in recent years. Taking commercial supercapacitors as an example, it contains many components, including packaging materials, current collectors, diaphragms, electrolytes, etc. that are not capacitively active in addition to capacitively active electrode materials. In practical applications, the mass proportion of inert components must be fully considered. When the electrode mass loading is low, the mass of the active material accounts for a small proportion of the overall device, resulting in a significant reduction in its performance in practical applications (based on the entire device). Therefore, increasing the loading amount of electrode active materials to commercial requirements (>10 mg cm -2 ,>100μm) has practical significance.
[0003] Natural wood is rich in cellulose, hemicellulose, and lignin, has a high carbon content, and has a high mass loading of the electrode after carbonization. However, the pore structure, chemical composition, and space / active material utilization of wood-based thick carbon electrodes still need to be further improved. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0005] As one aspect of the present invention, the present invention provides a method for preparing a wood-based thick carbon electrode material, which comprises the following steps:
[0006] (1) Slicing and cleaning natural wood to obtain wood chips;
[0007] (2) dissolving polyvinyl pyrrolidone and zinc nitrate in an alcohol solution to prepare a zinc nitrate alcohol solution; immersing the wood chips obtained in step (1) in the zinc nitrate alcohol solution, vacuum-assisted immersion, leaving overnight and then naturally drying to obtain wood chips loaded with zinc nitrate;
[0008] (3) The zinc nitrate loaded wood chips are heated to 250-280° C. in an air atmosphere, stabilized for 4-8 hours, replaced with a nitrogen atmosphere and heated to 800-1100° C. for carbonization, cooled, washed, and dried to obtain a wood-based thick carbon material.
[0009] As a preferred solution of the method for preparing the wood-based thick carbon electrode material of the present invention: the natural wood includes basswood.
[0010] As a preferred embodiment of the method for preparing the wood-based thick carbon electrode material of the present invention: in step (1), the cleaning comprises first cleaning with a dilute hydrochloric acid solution and then cleaning with water.
[0011] As a preferred embodiment of the method for preparing the wood-based thick carbon electrode material of the present invention: in step (2), the concentration of the polyvinyl pyrrolidone is 1 to 3 mg mL -1 , the concentration of zinc nitrate is 100~300mM.
[0012] As a preferred embodiment of the method for preparing the wood-based thick carbon electrode material of the present invention: in step (2), the concentration of the polyvinyl pyrrolidone is 2 mg mL -1 , the zinc nitrate concentration is 200 mM, and the alcohol solution includes ethanol solution.
[0013] As a preferred solution of the method for preparing the wood-based thick carbon electrode material of the present invention: the ethanol solution is an ethanol aqueous solution with a mass concentration of 70-75%.
[0014] The method for preparing a wood-based thick carbon electrode material is characterized in that: in step (3), the air atmosphere has an air flow rate of 100 to 300 sccm, and the nitrogen atmosphere has a nitrogen flow rate of 100 to 300 sccm.
[0015] As a preferred embodiment of the method for preparing the wood-based thick carbon electrode material described in the present invention: in step (3), the wood chips loaded with zinc nitrate are heated to 260°C in an air atmosphere, stabilized for 6 hours, with an air flow rate of 200 sccm, and then the temperature is increased to 1000°C for carbonization for 2 hours in a nitrogen atmosphere, with a nitrogen flow rate of 200 sccm.
[0016] Beneficial effects of the present invention: The present invention uses natural basswood as the base material, adsorbs an activator containing heteroatoms, and the thick carbon electrode after high-temperature carbonization has a unique expansion structure, a developed multi-level pore structure, and abundant heteroatom energy groups. It is used as a self-supporting electrode material for carbon-based double-layer supercapacitors and zinc ion hybrid supercapacitors, without the need for additional additives (such as conductive agents and adhesives), maximizing the utilization of electrode space / active materials and maximizing its capacitance performance. At the same time, its size, shape, thickness and other characteristics can be adjusted according to industrial needs.
[0017] Specifically, the natural wood of the present invention is based on raw materials, which is cheap, easy to obtain, non-toxic, and has the advantages of low process cost, economic efficiency, and no pollution. The mass load of the electrode after carbonization is high, which can meet the requirements of commercial supercapacitors for electrode mass load. Zinc nitrate is used as an activator / dopant, and a vacuum-assisted impregnation method is used to combine natural wood with zinc nitrate. Natural wood has abundant oxygen-containing functional groups, which can uniformly adsorb zinc ions through hydrogen bonding and complexation, and regulate its overall structure at the molecular level. The present invention adopts a one-step carbonization method to prepare a hierarchical porous wood-based thick carbon electrode material rich in nitrogen / oxygen cap energy groups, and directly controls the pore structure and surface chemical composition of the electrode material by controlling the carbonization temperature. During the heating process, the nitrate ions in the zinc nitrate decompose and produce a large amount of gas, which can expand the tight wood cell wall, and the three-dimensional space can be penetrated by the electrolyte, the electrolyte storage sites are increased, and the internal space utilization of the electrode is improved. In addition, during the heating process, zinc nitrate thermally decomposes to form ZnO nanoparticles, which then undergo a carbon thermal reduction reaction with the carbon skeleton formed by the carbonization of wood to be converted into Zn nanocrystals. The Zn nanocrystals can volatilize at 800°C, leaving nanopores. The intermediate products ZnO nanoparticles and Zn nanocrystals can not only act as hard templates to produce nanopores, providing storage sites and transmission channels for electrolyte ions, but also promote the thermal carbonization of carbon materials to form a partial graphitized structure, improve the conductivity of the carbonization product, and effectively improve the capacitance performance of the electrode. During the heating process, it was found that iron nitrate, cobalt nitrate, and nickel nitrate etched the carbon skeleton to generate a large number of nanopores, and had no expansion effect on the wood cell wall. The prepared hierarchical porous wood-based thick carbon material (ZnCW-1000) rich in nitrogen / oxygen corona energy groups, when used as electrode materials for carbon-based supercapacitors and zinc ion hybrid capacitors, still exhibits a high active material loading even in low temperature environments, has very excellent low temperature resistance, as well as high initial specific capacitance in low temperature environments, excellent rate performance, and outstanding cycle stability, and has practical application potential in the field of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0019] Figure 1 Schematic diagram of the preparation process of wood-based thick carbon electrode material ZnCW-T.
[0020] Figure 2Morphological characterization of wood-based thick carbon electrode materials CW, ZnCW-T, FeCW-1000, CoCW-1000, and NiCW-1000.
[0021] Figure 3 Structural characterization of wood-based thick carbon electrode materials CW and ZnCW-T series samples.
[0022] Figure 4 To characterize the chemical composition of wood-based thick carbon electrode materials CW and ZnCW-T series samples.
[0023] Figure 5 These are the capacitance performance test curves of wood-based thick carbon electrode materials CW, ZnCW-T series samples and FeCW-1000, CoCW-1000, and NiCW-1000 in the three-electrode system of supercapacitors.
[0024] Figure 6 These are the room temperature and low temperature capacitance performance test curves of the wood-based thick carbon electrode material ZnCW-1000 in the acidic supercapacitor double electrode system.
[0025] Figure 7 This is a photo of the actual application of supercapacitors using wood-based thick carbon material ZnCW-1000 as electrodes.
[0026] Figure 8 This paper tests the room temperature capacitance performance of zinc ion hybrid capacitors with wood-based thick carbon material ZnCW-1000 as positive electrode in 2MZnSO4 electrolyte.
[0027] Fig. 9 This paper tests the room temperature and low temperature capacitance performance of zinc ion hybrid capacitors with wood-based thick carbon material ZnCW-1000 as positive electrode in 3MZnClO4 electrolyte.
[0028] Fig.10 This is a performance comparison chart of wood-based thick carbon electrode materials ZnCW-1000 and ZnCW(N)-1000 in the three-electrode system of supercapacitors. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0030] Embodiment 1:
[0031] Materials and Chemicals:
[0032] Natural basswood was provided by Chenlin Model Material Factory Store. Zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and hydrochloric acid (36%) were provided by Nanjing Chemical Reagent Co., Ltd. Polyvinylpyrrolidone (PVP K30) and ethanol (75%) were provided by Sinopharm Chemical Reagent Co., Ltd. All water used was deionized water.
[0033] Step (1): natural basswood is cut into wood chips of 5 cm×5 cm×1 cm (length×width×height) perpendicular to its growth direction, cleaned with 0.1 M dilute hydrochloric acid, rinsed with deionized water until neutral, and then stored in an ethanol (75%) solution for later use.
[0034] Step (2): Add 0.1 g PVP (2 mg mL -1 ) and 2.97g Zn(NO3)2·6H2O (200mM) were dissolved in 50mL ethanol (75%) aqueous solution to prepare zinc nitrate ethanol solution. The pretreated wood chips were naturally dried, and 3 pieces (~4.5g) were immersed in 50mL zinc nitrate ethanol solution. After vacuum assisted immersion 3 times, they were left overnight to allow the ethanol solution to evaporate completely. After natural drying, wood loaded with zinc nitrate was obtained.
[0035] Step (3): Place the wood chips loaded with zinc nitrate in a tube furnace and heat at 5°C min -1 The temperature was raised to 260℃ at a rate of 100℃ and stabilized for 6 hours. The air flow rate during the heating process was 200sccm. After cooling naturally, the nitrogen atmosphere was replaced at 5℃min -1 The temperature was raised to 800℃ and carbonized for 2 hours at a heating rate of 200sccm during the heating process. After natural cooling, the sample was taken out, soaked in 0.1M dilute hydrochloric acid for 2 hours, washed with deionized water until neutral, and dried in a 60℃ forced air oven for 5 hours. The obtained wood-based thick carbon material was recorded as ZnCW-800.
[0036] Step (4): Cut the ZnCW-800 wood-based thick carbon material into 5mm×5mm×800μm (length×width×height) as the electrode material of the supercapacitor for testing and application, and the electrode mass is 7-8mg. The electrochemical test of the supercapacitor includes cyclic voltammetry test (CV) in a three-electrode system at room temperature, constant current charge and discharge test (GCD), rate performance test, AC impedance test, and long cycle performance test.
[0037] Specifically, in an alkaline three-electrode system at room temperature (6M KOH), two pieces of ZnCW-800 of similar mass are used as the working electrode and the counter electrode respectively, nickel foam is used as the current collector, an Hg / HgO electrode with a salt bridge (agar / saturated potassium chloride) is used as the reference electrode, and cellulose paper (NKK-MPF30AC-100, provided by CROOD) is used as a diaphragm. In an acidic three-electrode system at room temperature (H2SO4 with a mass fraction of 40%), a piece of ZnCW-800 is used as the working electrode, glassy carbon is used as the current collector, a graphite rod is used as the counter electrode, and an Ag / AgCl with a salt bridge (agar / saturated potassium chloride) is used as the reference electrode. The potential windows of CV and GCD in alkaline electrolytes are both -1 to 0V, and the potential windows of CV and GCD in acidic electrolytes are both 0 to 1V. The scan rate of CV is 5-100mVs -1 , the current density of GCD is 2-300 mA cm -1 , electrochemical impedance test frequency range 10 5 -10 -2 Hz, with an amplitude of 5mV.
[0038] Embodiment 2:
[0039] Step (1): Same as step (1) in Example 1.
[0040] Step (2): Same as step (2) in Example 1.
[0041] Step (3): the carbonization temperature is 900° C., and the remaining steps and parameters are the same as step (3) in Example 1. The obtained wood-based thick carbon material is recorded as ZnCW-900.
[0042] Step (4): The electrode material is ZnCW-900, and the three-electrode test is the same as step (4) in Example 1.
[0043] Embodiment 3:
[0044] Step (1): Same as step (1) in Example 1.
[0045] Step (2): Same as step (2) in Example 1.
[0046] Step (3): the carbonization temperature is 1000° C., and the remaining steps and parameters are the same as step (3) in Example 1. The obtained wood-based thick carbon material is recorded as ZnCW-1000.
[0047] Step (4): The electrode material is ZnCW-1000, and the three-electrode test is the same as step (4) in Example 1. In addition, the capacitive performance of the ZnCW-1000 electrode material is tested in a two-electrode system (normal temperature 25°C, low temperature 0, -20, -40°C). Two pieces of ZnCW-1000 of similar mass are used as the working electrode and the counter electrode, respectively, cellulose paper is used as the diaphragm, and H2SO4 with a mass fraction of 40% is used as the electrolyte to assemble a CR2032 button-type supercapacitor (denoted as ZnCW-1000 / / ZnCW-1000). The CV potential windows are all from 0 to 1V at 25°C, 0°C, and -20°C. At -40°C, the CV and GCD potential windows can be widened to 0-1.7V. The CV scan rate is 5-100mV s -1 , the current density of GCD is 2-200 mA cm -1 , electrochemical impedance test frequency range 10 5 -10 -2 Hz, with an amplitude of 5mV.
[0048] Take out the original battery in the digital electronic watch, charge a CR2032 button supercapacitor in step (4) to 1.7V at -40°C and connect it to the digital electronic watch, record the time change to demonstrate the practical application of the present invention in a low-temperature environment. Connect the two CR2032s in step (4) in series, charge them to 3.4V and connect them to a "ZCW" sign composed of 24 white-haired blue LED bulbs in parallel, record the color change of the sign to demonstrate the practical application of the present invention and its scalability. Connect the two CR2032s in step (4) in series, charge them to 3.4V at -40°C and connect them to a small blue fan blade equipped with a small motor, record the rotation state of the fan blade to demonstrate the practical application of the present invention and its scalability.
[0049] A CR2032 button-type zinc ion hybrid capacitor (ZnCW-1000 / / Zn) was assembled with ZnCW-1000 as the positive electrode, Zn sheet (200μm) as the negative electrode, and glass fiber membrane (Whatman GF / D) as the separator. Its capacitance performance was tested at room temperature using 2M ZnSO4 as the electrolyte. The potential window of CV and GCD was 0.2-1.8V.
[0050] Using 3M Zn(ClO4)2 as the electrolyte, the capacitance performance of zinc ion hybrid capacitor (ZnCW-1000 / / Zn) was tested at room temperature (25℃), 0℃, -20℃ and -40℃.
[0051] The two CR2032 button-type zinc ion hybrid capacitors in step (7) are connected in series and charged to 3.6V at -40°C, then connected to a signal light board (3V), and the signal change of the light board is recorded to demonstrate the practical application and scalability of the present invention in a low-temperature environment. The three CR2032 button-type zinc ion hybrid capacitors in step (7) are connected in series and charged to 5.4V at -40°C, then connected to a mobile phone (5V), and the power supply status of the mobile phone is recorded to demonstrate the practical application and scalability of the present invention in a low-temperature environment.
[0052] Embodiment 4:
[0053] Step (1): Same as step (1) in Example 1.
[0054] Step (2): Same as step (2) in Example 1.
[0055] Step (3): the carbonization temperature is 1100° C., and the remaining steps and parameters are the same as step (3) in Example 1. The obtained wood-based thick carbon material is recorded as ZnCW-1100.
[0056] Step (4): Same as step (4) in Example 1.
[0057] Comparative Example 1:
[0058] Step (1): Same as step (1) in Example 1.
[0059] Step (2): Place the wood in step (1) into a tubular furnace, as in step (3) in Example 1, and the obtained wood-based thick carbon material is recorded as CW.
[0060] Step (3): The electrode material is CW, and the three-electrode test is the same as step (4) in Example 1.
[0061] Comparative Example 2:
[0062] Iron nitrate nonahydrate (Fe(NO3)3·9H2O) or cobalt nitrate hexahydrate (Co(NO3)2·6H2O) or nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was provided by Nanjing Chemical Reagent Co., Ltd.
[0063] Step (1): Same as step (1) in Example 1.
[0064] Step (2): Add 0.1 g PVP (2 mg mL -1) and 4.04g Fe(NO3)3·9H2O (200mM) or 2.91g Co(NO3)2·6H2O (200mM) or 2.91g Ni(NO3)2·6H2O were dissolved in 50mL ethanol (75%) solution in turn to prepare ferric nitrate ethanol solution, cobalt nitrate ethanol solution and nickel nitrate ethanol solution respectively. The pretreated wood chips were naturally dried, and 3 pieces (~4.5g) were immersed in 50mL nitrate ethanol solution. After vacuum assisted immersion 3 times, they were left overnight to allow the ethanol solution to evaporate completely. After natural drying, nitrate-loaded wood was obtained.
[0065] Step (3): Same as step (3) in Example 1
[0066] Step (4): The electrode materials are FeCW-1000, CoCW-1000, and NiCW-1000, and the three-electrode test is the same as step (4) in Example 1.
[0067] Comparative Example 3:
[0068] Step (1): Same as step (1) in Example 1.
[0069] Step (2): Same as step (2) in Example 1.
[0070] Step (3): Place the wood chips loaded with zinc nitrate in a tube furnace and heat at 5°C min -1 The temperature was raised to 1000℃ and carbonized for 2 hours at a heating rate of 200sccm during the heating process. After natural cooling, the sample was taken out, soaked in 0.1M dilute hydrochloric acid for 2 hours, washed with deionized water until neutral, and dried in a 60℃ forced air oven for 5 hours. The obtained wood-based thick carbon material was recorded as ZnCW(N)-1000.
[0071] Morphology and structure characterization:
[0072] Figure 2 The morphology of wood-based thick carbon electrode materials CW and ZnCW-T is characterized. Specifically, Figure 2 (a, b) are scanning electron microscope (SEM) images of the CW cross section and longitudinal section, respectively. It can be observed from the figure that the structure of wood can be well inherited after carbonization, and the abundant micron-scale vertical channels provide buffer space and longitudinal transmission channels for the electrolyte. At the same time, the large number of pit structures on the vertical channel walls of carbonized wood can provide a path for the lateral transmission of electrolyte between channels. Figure 2 (c) is the transmission electron microscopy (TEM) image of CW, which shows the dense amorphous carbon structure of CW. Figure 2(d, e) are SEM images of the cross section and longitudinal section of ZnCW-1000. Compared with CW, it can be seen that the thick and dense cell wall of wood is expanded by the gas produced during the heating process of nitrate, and the three-dimensional space formed can be penetrated by electrolytes, the contact surface between the electrode and the electrolyte is increased, the number of active sites is increased, and the utilization rate of the electrode space is improved. Figure 2 (f) is the TEM image of ZnCW-1000. Compared with CW, ZnCW-1000 has more abundant nanopores in its microstructure. This is because during the heating process, zinc nitrate thermally decomposes to form ZnO nanoparticles, which then undergo a carbon thermal reduction reaction with the carbon skeleton formed by the carbonization of wood to convert into Zn nanocrystals. The Zn nanocrystals evaporate at a temperature ≥ 800°C, leaving nanopores. The intermediate products ZnO nanoparticles and Zn nanocrystals can not only act as hard templates to produce nanopores, providing storage sites and transmission channels for electrolyte ions, but also promote the pyrolysis and carbonization of carbon materials to form a partially graphitized structure, improve the conductivity of the carbonization product, and effectively improve the capacitance performance of the electrode. Figure 2 (gi) are the SEM images of ZnCW-800, ZnCW-900 and ZnCW-1100, respectively. It can be observed that with the increase of carbonization temperature, the expansion effect of wood cell wall becomes more obvious. However, when the carbonization temperature is too high, over-activation will cause partial collapse of the three-dimensional structure. Figure 2 (jI) are SEM images of FeCW-1000, CoCW-1000, and NiCW-1000. Compared with the unique expansion structure of the ZnCW-T series samples, it was found that iron nitrate, cobalt nitrate, and nickel nitrate had no expansion effect on the wood cell wall. Iron nitrate, cobalt nitrate, and nickel nitrate mainly had an etching effect, and the carbon wall became rough and porous.
[0073] Figure 3 The structural characterization of the wood-based thick carbon electrode material CW and ZnCW-T series samples. Specifically, it can be seen from the X-ray diffraction pattern ( Figure 3 (a)), both CW and ZnCW-T exhibit a broad diffraction peak (002) near 23° and a weak diffraction peak (101) near 43°, indicating the amorphous carbon structure of the samples. Figure 3 (b) shows the Raman spectra of CW and ZnCW-T series samples, revealing the effects of zinc nitrate activation and carbonization temperature on the degree of graphitization of the wood-based carbon skeleton. It can be clearly observed that the carbon nanotubes at 1350 cm -1 (D peak) and 1590cm -1 The two characteristic peaks (G peak) correspond to sp 3 Hybridization of defective / disordered amorphous carbon with sp 2 Hybridized ordered graphitic carbon. D / I GThe value of I can measure the degree of graphitization of carbon materials. D / I G The values of are 1.09, 1.13, 1.09, 1.07, and 1.06, respectively, all greater than 1, which again reveals the amorphous carbon structure of CW and ZnCW-T samples. D / I G After zinc nitrate activation, the carbon skeleton becomes more disordered and has more defect sites, which reflects the activation and pore-forming effect of zinc nitrate. D / I G As the temperature increases, the graphitization degree of the charcoal skeleton becomes better. On the one hand, high-temperature carbonization is beneficial to the conductivity of the carbon skeleton. On the other hand, ZnO nanoparticles and Zn nanocrystals can promote the pyrolysis and carbonization of carbon materials, forming a partial short-range graphite domain structure, which improves the conductivity of the carbon skeleton. Figure 3 (c) The specific surface area, pore volume and micropore ratio of CW and ZnCW-T samples were quantitatively analyzed, and the specific results are listed in Table 1. Figure 3 (d) is the pore size distribution diagram of CW and ZnCW-T samples obtained by non-local density functional theory (NLDFT) analysis based on nitrogen adsorption-desorption curves. The wood-based thick carbon electrode obtained by direct carbonization of wood is mainly composed of micropores, with almost no mesopores. The pore size is concentrated around 1 nm, and the specific surface area is only 204.8 m 2 g -1 , the pore volume is only 0.13cm 3 g -1 After activation by zinc nitrate, the micropores and mesopores (2-10 nm) of ZnCW-800 increased significantly, and the specific surface area increased to 715.6 m 2 g -1 When the carbonization temperature rises to 900℃, the proportion of mesopores in the carbon skeleton increases, which is the reason why the specific surface area of ZnCW-900 is lower than that of ZnCW-800. When the carbonization temperature rises to 1000℃, the carbon thermal reduction reaction of ZnO and the carbon skeleton and the high-temperature migration and volatilization of Zn nanocrystals are more thorough, and the pore volume of the carbon skeleton is greatly increased and mainly mesopores. The specific surface area, pore volume, and micropore proportion of ZnCW-1000 are 1115.5m 2 g -1 、0.69cm 3 g -1, 50.4%. However, when the carbonization temperature rises to 1100℃, over-activation causes partial collapse of the pore structure, and the specific surface area and pore volume of ZnCW-1100 decrease. The pore characteristics of the electrode are crucial to the capacitance performance. Micropores provide active sites for the adsorption / desorption of electrolyte ions, and mesopores provide channels for the transmission of electrolyte ions. Large specific surface area, high pore volume, and appropriate micro / mesopore ratio ensure high initial specific capacitance and excellent rate performance of the electrode.
[0074] Table 1 Pore properties of CW, ZnCW-800, ZnCW-900, ZnCW-1000 and ZnCW-1100.
[0075]
[0076] The elemental composition / content and valence state of the sample surface were further analyzed by X-ray photoelectron spectroscopy (XPS) of the sample. Figure 4 (a) is the XPS total spectrum of CW and ZnCW-T series samples. It can be seen that CW is mainly composed of carbon and oxygen elements, while additional nitrogen elements are observed in ZnCW-T series samples. Figure 4 (b) The atomic percentages of nitrogen and oxygen in CW and ZnCW-T series samples are summarized by bar graphs. The oxygen content in CW is 12.8%. After activation by zinc nitrate, the nitrogen and oxygen contents in the samples both increase first and then decrease. The former is due to the doping of the nitrogen and oxygen in the nitrate of zinc nitrate with the wood-derived carbon skeleton during the carbonization process, and the latter is due to the decrease in the stability of the heteroatom energy group with the increase of carbonization temperature, especially when the carbonization temperature rises to 1100℃, the heteroatom content in the carbon skeleton is greatly reduced. Specifically, the nitrogen content of ZnCW-800, ZnCW-900, ZnCW-1000 and ZnCW-1100 is 2.3%, 2.2%, 2.0% and 1.4%, respectively, and the oxygen content is 13.2%, 13.0%, 12.7% and 8.6%, respectively. The elemental valence states of nitrogen and oxygen species in the ZnCW-T series samples were further analyzed by XPS high-resolution spectra. Figure 4As shown in (c), pyridinic nitrogen (N-6) at 398.3-398.6 eV, pyrrolic nitrogen (N-5) at 399.7-400.3 eV, graphitic nitrogen (NQ) at 401.4-401.9 eV, and oxidized nitrogen (NX) at 404.8-405.0 were observed in the high-resolution N1s spectrum. N-6 and N-5 contribute additional pseudocapacitance to the electrode through redox reactions, and NQ provides additional electrons to carbon atoms, thereby improving the conductivity of the carbon skeleton and thus the capacitive performance of the electrode. In ZnCW-800, the nitrogen species is mainly N-5, about 63.3%. With the increase of carbonization temperature, more N-6 or N-5 located in defective / edge carbon are pyrolyzed, and the carbon skeleton is mainly composed of NQ stabilized in the carbon ring. In ZnCW-1000, the NQ content is as high as 50.4%. As shown Figure 4 As shown in (d), C=O (OI) at 531.6-531.9 eV, C-OH (O-II) at 532.6-532.8 eV, and COOH (O-III) at 533.6-533.8 eV were observed in the high-resolution O1s spectrum. With the increase of carbonization temperature, more double bonds in Ol are opened and reduced to O-ll, while the content of O-III does not change much. The contents of OI, O-II, and O-III in ZnCW-1000 are 29.4%, 39.6%, and 31%, respectively. The introduction of oxygen-containing functional groups can not only improve the hydrophilicity of the electrode and reduce the contact resistance at the electrode / electrolyte interface, but also contribute additional pseudocapacitance through redox reactions, thereby improving the capacitive performance of the electrode.
[0077] Electrochemical performance test:
[0078] Firstly, the capacitive performance of the wood-based thick carbon electrode material was evaluated in a three-electrode system. Figure 5 (a)) and acid electrolyte ( Figure 5 (b)) is 10 mV s -1 The CV curve of the wood-based thick carbon electrode was recorded at a scanning rate of . The capacitance performance of the electrode can be preliminarily judged from the size of the closed area of the CV curve. For CW, its narrow micropores limit the effective adsorption / desorption of electrolyte ions, the CV curve is "liver-shaped", and the capacitance performance is poor. Compared with CW, the closed area of the CV curve of the ZnCW-T series samples is significantly increased in both alkaline and acidic electrolytes, and the electrode capacitance performance is significantly improved. Moreover, with the increase of the carbonization temperature, the enclosed area of the CV curve increases first and then decreases (CW<ZnCW-1100<ZnCW-800<ZnCW-900<ZnCW-1000), and the closed area of the CV curve of the ZnCW-T series samples in acidic electrolytes is larger, and the pseudocapacitance hump is more obvious. The pre-oxidation process is beneficial to the electrode capacitance performance, such as Fig.10 (a) shows that at 10mVs -1 The enclosed area of the CV curve of ZnCW-1000 at the scanning rate is significantly larger than that of ZnCW(N)-1000. Based on the GCD curve of the electrode ( Fig.10 (b, c)) Calculate the specific capacitance of the two and draw the corresponding rate performance curve ( Fig.10 (d)), when the current density is 2 mA cm -2 When ZnCW(N)-1000 and ZnCW-1000 have specific capacitances of 6354.0 mF cm -2 and 9442.2mF cm -2 In addition, the capacitance performance of ZnCW-1000 electrode was compared with that of FeCW-1000, CoCW-1000 and NiCW-1000 electrodes in alkaline electrolyte. Figure 5 As can be seen from (c), the capacitance performance of the former is significantly higher than that of the latter three. Specifically, when the current density is 5 mA cm -2 When the area capacitance of ZnCW-1000, FeCW-1000, CoCW-1000 and NiCW-1000 is 7201.1mF cm -2 、1045.4mF cm -2 、865.3mF cm -2 and 686.8 mF cm -2 , proving that compared with the etching effects of iron nitrate, cobalt nitrate, and nickel nitrate, the unique expansion and pore-forming effect of zinc nitrate has the greatest gain in electrode capacitance performance. Therefore, the present invention systematically studies the capacitance performance of ZnCW-T series samples. ZnCW-1000 was selected for testing in an acidic electrolyte. Figure 5 (d) is the ZnCW-1000 at a scan rate of 5-100mVs -1 The CV curve at low scan rate is a quasi-rectangular shape with a hump. The wide hump is caused by the redox reaction of nitrogen / oxygen functional groups with pseudocapacitive activity. As the scan rate increases, the internal resistance of the electrode increases, and the CV curve gradually becomes a spindle shape. Figure 5 (e) is the GCD curve of ZnCW-1000. The linear quasi-triangular shape shows the typical double-layer capacitance characteristics of the electrode. As the current density increases, the voltage drop caused by the internal resistance becomes more obvious and the capacitance gradually decays. Figure 5 (f) is the electrochemical impedance spectrum of ZnCW-T series samples. As the carbonization temperature increases, the hydrophilic nitrogen / oxygen functional groups gradually pyrolyze, the content decreases, and the contact internal resistance between the electrode and the electrolyte increases. The internal resistance (R s) are 2.2Ω, 2.4Ω, 2.6Ω and 2.8Ω respectively. As the carbonization temperature increases, the conductivity of the carbon skeleton increases and the charge transfer impedance (R ct ) are 0.25Ω, 0.21Ω, 0.08Ω and 0.12Ω respectively. The small charge transfer impedance is conducive to the transfer of charge under high current density. The specific capacitance of the electrode is calculated based on the GCD curve. Figure 5 (g, h) are the corresponding rate performance curves. When the current density is 2 mA cm -2 When the area specific capacitance (C A ) are 10564.1, 11696.9, 11962.8 and 8101mF cm -2 , the corresponding mass specific capacitance (C g ) are 347.5, 384.8, 393.5 and 266.5 F g respectively -1 When the current density increases to 300 mA cm -2 When the specific capacitance of ZnCW-800, ZnCW-900, ZnCW-1000 and ZnCW-1100 is 4400mF cm -2 (145.1Fg -1 )、5090.9mFcm -2 (174.5F g -1 )、6352.9mF cm -2 (209.7F g -1 ) and 3451.6mF cm -2 (113.3F g -1 ). Among the ZnCW-T series samples, ZnCW-1000 has the best initial specific capacitance and rate performance. On the one hand, thanks to its well-developed hierarchical porous structure and suitable micro / mesopore ratio, a large number of ion-accessible micropores provide effective active sites for the adsorption / desorption of electrolyte ions, and the well-developed small mesopores provide a path for the transmission of electrolyte ions. On the other hand, the abundant nitrogen / oxygen functional groups in ZnCW-1000 contribute additional pseudocapacitance to the electrode, and the nitrogen-containing functional groups are mainly NQ, which enhances the conductivity of the electrode and is beneficial to its rate performance. In addition, ZnCW-1000 also has excellent cycle stability, such as Figure 5 As shown in (i), the electrode is at 50 mA cm -2 After 50,000 cycles of charge / discharge at a current density of , the coulombic efficiency and specific capacitance have almost no change.
[0079] In practical applications, the electrodes of energy storage devices must not only achieve a large load of active materials, but also be able to withstand harsh environments. The lack of porosity in CW makes it have no capacitance performance in harsh low-temperature environments. In order to evaluate the practical application potential of wood-based thick carbon electrode material ZnCW-1000, symmetrical button capacitor devices (ZnCW-1000 / / ZnCW-1000, dual-electrode system) were assembled and their capacitance performance was evaluated at different temperatures. Figure 6 (a) is the scanning rate of 5 mV s -1 CV curves of ZnCW-1000 at 25°C, 0°C, -20°C, and -40°C. Although the transmission rate of electrolyte ions and the reaction rate of pseudocapacitive redox slow down with decreasing temperature, and the closed area of the CV curve tends to decrease, the abundant vertical channels and developed hierarchical porous structure of ZnCW-1000 ensure the effective adsorption / desorption and smooth transmission of electrolyte ions, and its capacitance does not decrease significantly with temperature. In addition, limited by the decomposition potential of water, the operating voltage of conventional aqueous supercapacitor devices generally does not exceed 1.23V. Low temperature can reduce the dynamics of water molecules and inhibit the decomposition of water molecules during long-term charging and discharging. At an extremely cold temperature of -40°C, the potential window of ZnCW-1000 / / ZnCW-1000 in the present invention can be widened to 0-1.7V. From -40°C, ZnCW-1000 at a scanning rate of 5-100mV s -1 CV curve diagram when Figure 6 As can be seen from (b, c), the CV curve does not show obvious distortion at high potential (1.7 V), and the device can work stably in the range of 0-1.7 V. At -40 °C, ZnCW-1000 / / ZnCW-1000 has a high current density of 2-200 mA cm -1 The linear quasi-symmetric triangular GCD curve ( Figure 6 (d, e)) also confirmed the effective storage and transport of electrolyte ions at ultra-low temperatures. As the temperature decreases, the R ct Gradually increase, such as Figure 6 As shown in (f), they are 0.1Ω (25℃), 1.1Ω (0℃), 1.3Ω (-20℃) and 1.9Ω (-40℃) respectively. Figure 6 (g) is the rate performance curve of ZnCW-1000 / / ZnCW-1000 at different temperatures. -2 , the device's area specific capacitance (C A ′) are 4572.5, 3910.7, 3842.4 and 4563.5 mF cm -2 , the corresponding mass specific capacitance (C a′) were 169.7, 141.5, 137.2 and 169.4 F g -1 The current density increases 100 times (200 mA cm -2 ), the specific capacitance of the device at different temperatures is 3276.2mF cm -2 (117.0F g -1 )、2970.5mF cm -2 (106.9F g -1 )、2823.5mF cm -2 (100.5F g -1 ) and 2362.5mF cm -2 (85.0F g -1 ). ZnCW-1000 / / ZnCW-1000 exhibits amazing long-term durability in low temperature environments (-40°C), such as Figure 6 As shown in (h), at a current density of 50 mA cm -2 The specific capacitance has almost no attenuation after 100,000 charge and discharge cycles. In addition, energy density / power density is an important indicator for evaluating the practical application potential of energy storage devices. The maximum energy density and power density of ZnCW-1000 / / ZnCW-1000 are 1.8 mWh cm -2 (64.0Wh kg -1 ) and 160.3 mW cm -2 (5714.3W kg -1 ),like Figure 6 As shown in (i), the device of the present invention builds a bridge between the energy density and power density of traditional capacitors and secondary batteries.
[0080] Figure 7 The practical application of ZnCW-1000 / / ZnCW-1000 devices in harsh environment (-40℃) was further demonstrated. Figure 7 (a) is a schematic diagram of the button-type supercapacitor CR2032 and its series connection mentioned in the present invention. The working potential of a single device is 1.7V. By connecting two devices in series, the working potential of the circuit can be expanded to 3.4V. Figure 7 As shown in (b, c), the CV and GCD curves of the circuit with two devices in series have no obvious distortion in the voltage range of 0-3.4V, which proves the scalability of the present invention. Figure 7 As shown in (d), a single device (SSC) can power an electronic watch for more than half an hour. Figure 7 As shown in (e), two devices in series (SSCs) can light up the ZCW" sign composed of 24 white-haired blue light bulbs in parallel. Figure 7As shown in (f), two devices connected in series (SSCs) can drive a small blue fan equipped with a small motor. The above application intuitively demonstrates the practicality of the present invention.
[0081] Based on the above analysis, ZnCW-1000 has vertical channels, a well-developed multi-level pore structure, and abundant heteroatom energy groups. ZnCW-1000 can be used as an electrode material for high-performance zinc ion capacitors. Figure 8 As shown in (a), zinc ion capacitors are an emerging hybrid energy storage device that stores energy through the adsorption / desorption of electrolyte ions on carbon-based positive electrodes and the reversible deposition / dissolution of zinc ions on zinc-based negative electrodes. ZnSO4 aqueous solution is one of the most commonly used electrolytes for zinc ion hybrid capacitors. 2M ZnSO4 aqueous solution was selected as the electrolyte to evaluate the capacitive performance of ZnCW-1000-based zinc ion hybrid capacitors (ZnCW-1000 / / Zn). At 5-100mV s -1 The CV curve is recorded within the scanning rate range. Figure 8 As shown in (b), the CV curve can operate stably in the voltage range of 0.2V-1.8V, and presents a quasi-rectangular shape accompanied by a wide hump at low scan rate. As the scan rate increases, due to the increase in internal resistance, the CV curve gradually becomes shuttle-shaped, proving the coexistence of fast electrochemical double-layer capacitance and surface pseudocapacitance caused by heteroatom clusters. Figure 8 (c) and Figure 8 (d) shows the current density between 2 and 200 mA cm -2 The linear quasi-triangular shape of the GCD curve also proves the fast kinetics of the electrode. Based on the GCD curve, the specific capacitance of the electrode was calculated according to the formula, and the corresponding rate performance curve and the Lagon curve were plotted on Figure 8 (e) with Figure 8 (f). Specifically, ZnCW-1000 / / Zn at 2 mA cm -2 The current density provided 4932.5mF cm -2 (61.7F cm -3 , 176.2F g -1 ) with a high initial specific capacitance of 1.8 mWh cm -2 (21.9mWh cm -3 , 62.6Wh kg -1 ) with a high energy density. As the current density increases, the specific capacitance gradually decreases due to the hysteresis of the pseudocapacitive reaction and the inability to fully utilize the active materials in the thick electrode. However, the developed multi-level pore structure and stable self-supporting carbon skeleton of Zn-1000 ensure its good rate performance. Even if the current density increases to 200 mA cm -2 , the specific capacitance remains at 2518.0mF cm-2 (31.5F cm -3 , 90.0F g -1 ), and the power density is 100.0 mW cm -2 (1250.0mW cm -3 , 3571.4W kg -1 ). At 50 mA cm -2 The cycling durability of the zinc ion hybrid capacitor was evaluated at a high current density of 1.5 Å, and it can still maintain 91.5% of its initial specific capacitance after 30,000 cycles. These results confirm the great potential of ZnCW-1000 as an electrode material for zinc ion hybrid capacitors.
[0082] Similarly, the development of high-performance low-temperature zinc ion capacitors is crucial for their application in harsh environments. Although zinc ion hybrid capacitors using ZnSO4 as the electrolyte exhibit good capacitance performance at room temperature, the ZnSO4 electrolyte freezes at low temperatures, causing device failure. Therefore, antifreeze 3M Zn(ClO4)2 was selected as the electrolyte to further evaluate the application potential of ZnCW-1000 / / Zn under harsh conditions. Zn(ClO4)2 solution contains water molecules and ClO4 - Ion-coordinated solvated Zn 2+ clusters, while water molecules and Zn 2+ The interaction between ions is stronger than the interaction between water molecules, which significantly reduces the aggregation of water molecules and weakens the hydrogen bonds inside the solution. In addition, there are two solvation shells outside the zinc ion. The first solvation shell is composed of six water molecules, while the second solvation shell is composed of ClO4 - The second solvation shell blocks the interaction between the water molecules in the first solvation shell and the water molecules in the bulk phase, which also destroys the hydrogen bond network between water molecules. The destruction of the hydrogen bond network between water molecules in the 3M ZnClO4 electrolyte inhibits its freezing in low temperature environments.
[0083] Fig. 9 (a) shows the CV curves of ZnCW-1000 / / Zn at different temperatures (25°C, 0°C, -20°C and -40°C) using 3M ZnClO4 electrolyte. As the temperature decreases, the enclosed area of the CV curve gradually decreases due to the decrease in ionic conductivity and the slow ion transport and pseudocapacitive reaction dynamics. In addition, since low temperature inhibits the decomposition kinetics of water, the potential window of ZnCW-1000 / / Zn can be widened to 0.2-2V at -40°C. Fig. 9As shown in (b), the GCD curve of ZnCW-1000 / / Zn at -40°C is linear and quasi-triangular, and no obvious distortion is observed, which proves that the device can operate stably in the voltage range of 0.2V-2V. -2 When the specific capacitance of ZnCW-1000 / / Zn is 6088.75mFcm at room temperature -2 (76.1Fcm -3 , 217.5F g -1 ), when the temperature drops to 0℃, -20℃, and -40℃, the specific capacitance can still maintain 92.5%, 84.1%, and 73.9%, respectively. When the current density increases to 100mA cm -2 When the specific capacitance of ZnCW-1000 / / Zn at 0℃, -20℃, and -40℃ is 94.4%, 78.4%, and 58.8% of that at room temperature, respectively. Fig. 9 (c)). In addition, the ZnCW-1000 electrode also inherits its excellent cycling stability at room temperature at low temperatures. Fig. 9 As shown in (d), ZnCW-1000 / / Zn at 30 mA cm -2 After 20,000 charge and discharge cycles at the same current density, the specific capacitance retention rates were 92.8% and 90.1% at room temperature and -40°C, respectively. Fig. 9 (e) with Fig. 9 (f) The practical application potential of the zinc ion hybrid capacitor prepared in the present invention is intuitively demonstrated. Even in a harsh environment (-40°C), two ZnCW-1000 / / Zn devices (3.6V) connected in series can light up an LED sign (3V), and three devices (5.4V) connected in series can drive a mobile phone (5V) to operate.
[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. Application of a wood-based thick carbon electrode material in a high-performance capacitor, characterized in that: The method for preparing the wood-based thick carbon electrode material comprises the following steps: (1) Slicing and cleaning natural basswood to obtain wood chips; (2) dissolving polyvinyl pyrrolidone and zinc nitrate in an alcohol solution to prepare an alcohol solution of zinc nitrate; impregnating the wood chips obtained in step (1) in the alcohol solution of zinc nitrate, vacuum-assisted impregnation, leaving the mixture overnight and then naturally drying the mixture to obtain wood chips loaded with zinc nitrate; (3) heating the zinc nitrate loaded wood chips to 260° C. in an air atmosphere, stabilizing for 6 h at an air flow rate of 200 sccm, changing to a nitrogen atmosphere and heating to 1000° C. for carbonization for 2 h at a nitrogen flow rate of 200 sccm, thereby obtaining a wood-based thick carbon electrode material; In step (2), the concentration of polyvinyl pyrrolidone is 2 mg mL -1 , the concentration of zinc nitrate is 200 mM; the alcohol solution is an ethanol aqueous solution with a mass concentration of 70-75%; The high performance capacitor is assembled by using 40% by mass H2SO4 or 3 M ZnClO4 as the electrolyte; The high performance capacitor can be used in low temperature environments.
2. The use according to claim 1, characterized in that: In step (1), the cleaning includes first cleaning with a dilute hydrochloric acid solution and then cleaning with water.
3. The use according to claim 1 or 2, characterized in that: The wood-based thick carbon electrode material can be used in a three-electrode system or a two-electrode system.
Citation Information
Patent Citations
Bamboo-like carbon nanotube composite material based on wood carbonized porous structure and preparation method of bamboo-like carbon nanotube composite material
CN114314563A